Music of Razak Abdul Aziz: Preparing Chosen Solo and Collaborative Piano Works for Two Academic Recitals - Mohd Fairuz Zamani (Wacana Seni Journal of Arts Discourse, 2021)
For the first time in history, full-scale performances on musical compositions by a Malaysian composer, Razak Abdul Aziz, were presented through two academic recitals—27 July 2019 and 6 February 2020—at Orchestra Hall, Akademi Seni Budaya dan Warisan Kebangsaan (ASWARA). These recitals consisted of solo and collaborative piano works, performed by me and a team of music collaborators that were specifically selected for this purpose. Razak Abdul Aziz, who is still actively composing, spent most of his career life as an academic, first serving for Institut Teknologi MARA (ITM), then Universiti Sains Malaysia (USM) until his retirement in November 2019. Besides fulfilling the academic requirements set by Universiti Pendidikan Sultan Idris (UPSI) for my doctoral degree, I had chosen to perform works by this composer as he is generally known to the local music community as one of the earliest contemporary composers in the country (started composing in the 1980s). Yet, a full-scale performance of his works was long overdue, though he had the opportunities to have some of his works premiered and performed on local and international platforms as part of concert programmes. This artist project talks about the preparation I made for both recitals, briefly explaining the creative process I journeyed through and the challenges I faced during this time span, discussing each work I had selected for these academic recitals. These recitals could, perhaps, be the pioneers in studying and performing works by Razak Abdul Aziz, hoping to expand this effort to national and international levels.